Handbook of multilevel analysis - Leeuw, Jan de (Springer, 2008)
Multilevel analysis is the statistical analysis of hierarchically and non-hierarchically nested data. Multilevel data are especially prevalent in the social and behavioral sciences and in the bio-medical sciences. This book presents the state of the art in multilevel analysis, with an emphasis on more advanced topics.